A 60‐heme reductase complex from an anammox bacterium shows an extended electron transfer pathway. Issue 3 (5th April 2019) - Dietl, Andreas; Maalcke, Wouter J.; Ferousi, Christina; Jetten, Mike S. M.; Kartal, Boran; Barends, Thomas R. M.
Abstract : The heterododecameric complex of a reducing octaheme cytochrome c with its redox partner shows an extended electron transfer pathway. Abstract : The hydroxylamine oxidoreductase/hydrazine dehydrogenase (HAO/HDH) protein family constitutes an important group of octaheme cytochromes c (OCCs). The majority of these proteins form homotrimers, with their subunits being covalently attached to each other via a rare cross‐link between the catalytic heme moiety and a conserved tyrosine residue in an adjacent subunit. This covalent cross‐link has been proposed to modulate the active‐site heme towards oxidative catalysis by distorting the heme plane. In this study, the crystal structure of a stable complex of an HAO homologue (KsHAOr) with its diheme cytochrome c redox partner (KsDH) from the anammox bacterium Kuenenia stuttgartiensis was determined. KsHAOr lacks the tyrosine cross‐link and is therefore tuned to reductive catalysis. The molecular model of the KsHAOr–KsDH complex at 2.6 Å resolution shows a heterododecameric (α6 β6 ) assembly, which was also shown to be the oligomeric state in solution by analytical ultracentrifugation and multi‐angle static light scattering. The 60‐heme‐containing protein complex reveals a unique extended electron transfer pathway and provides deeper insights into catalysis and electron transfer in reductive OCCs.